9-[2-(Phosphonomethoxy)propyl]adenine (PMPA) Therapy Prolongs Survival of Infant Macaques Inoculated with Simian Immunodeficiency Virus with Reduced Susceptibility to PMPA - van Rompay, Koen K. A. (American Society for Microbiology, 1999)
Simian immunodeficiency virus (SIV) infection of newborn rhesus macaques is a useful animal model of human immunodeficiency virus infection for the study of the emergence and clinical implications of drug-resistant viral mutants. We previously demonstrated that SIV-infected infant macaques receiving prolonged treatment with 9-[2-(phosphonomethoxy)propyl]adenine (PMPA) developed viral mutants with fivefold reduced susceptibility to PMPA in vitro and that the development of these mutants was associated with the development of a K65R mutation and additional compensatory mutations in reverse transcriptase (RT). To study directly the virulence and clinical implications of these SIV mutants, two uncloned SIV(mac) isolates with similar fivefold reduced in vitro susceptibilities to PMPA but distinct RT genotypes, SIV(mac055) (K65R, N69T, R82K A158S, S211N) and SIV(mac385) (K65R, N69S, I118V), were each inoculated intravenously into six newborn rhesus macaques; 3 weeks later, three animals of each group were started on PMPA treatment. All six untreated animals developed persistently high levels of viremia and fatal immunodeficiency within 4 months. In contrast, the six PMPA-treated animals, despite having persistently high virus levels, survived significantly longer: 5 to 9 months for the three SIV(mac055)-infected infants and ≥21 months for the three SIV(mac385)-infected infants. Virus from only one untreated animal demonstrated reversion to wild-type susceptibility and loss of the K65R mutation. In several other animals, additional RT mutations, including K64R and Y115F, were detected, but the biological role of these mutations is unclear since they did not affect the in vitro susceptibility of the virus to PMPA. In conclusion, this study demonstrates that although SIV(mac) mutants with the PMPA-selected K65R mutation in RT were highly virulent, PMPA treatment still offered strong therapeutic benefits. These results suggest that the potential emergence of HIV mutants with reduced susceptibility to PMPA in patients during prolonged PMPA therapy may not eliminate its therapeutic benefits.